2021
DOI: 10.1111/os.12895
|View full text |Cite
|
Sign up to set email alerts
|

Early Patellofemoral Function of Medial Pivot Prostheses Compared with Posterior‐Stabilized Prostheses for Unilateral Total Knee Arthroplasty

Abstract: Objective: To systematically evaluate the patellofemoral joint design of medial pivot prosthesis, which incorporates a variety of "patella-friendly" design features, by comparing clinical and radiographic results with another prosthesis. Methods: All consecutive patients who underwent unilateral total knee arthroplasty (TKA) with medial pivot prosthesis (Group MP, 126 cases) between September 2016 and April 2018 were enrolled in this retrospective study. For each patient reviewed, a control patient was matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 50 publications
(65 reference statements)
0
15
0
Order By: Relevance
“…Posterior stabilized (PS) TKAs utilise the cam-post mechanism whereby the cam-post articulates with the tibial post improving femoral rollback and at the same time providing sagittal stability (8)(9)(10)(11)(12). Despite this it is associated with central tibial impingement and increased bleeding intra-operatively secondary to the larger osteotomy (13). Moreover, these alteration in the normal knee kinematic might contribute to the knee function and the survival of the prothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Posterior stabilized (PS) TKAs utilise the cam-post mechanism whereby the cam-post articulates with the tibial post improving femoral rollback and at the same time providing sagittal stability (8)(9)(10)(11)(12). Despite this it is associated with central tibial impingement and increased bleeding intra-operatively secondary to the larger osteotomy (13). Moreover, these alteration in the normal knee kinematic might contribute to the knee function and the survival of the prothesis.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 13 studies reported ROM [ 4 , 5 , 8 , 11 , 18 , 19 , 21 25 , 30 , 32 ]. Since high heterogeneity was indicated ( I 2 = 77%, P < 0.1), sensitivity analyses were conducted.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of KSS between the MP group and PS group was recorded in 10 studies [ 8 , 11 , 18 , 19 , 21 , 22 , 24 , 26 , 28 , 32 ].The included studies had significant heterogeneity ( I 2 = 89%, P < 0.1), and there was no change after sensitivity analysis. Random-effects model analysis showed that no significant difference in postoperative KSS existed between the MP group (867 knees) and PS group (809 knees) (MD = − 0.83, 95% CI − 3.01–1.35, P = 0.45) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations